Dagnosis Kesulitan Belajar Dalam Perspektif al-Qur’an - Fatih, Tanuri Abu; Khotimah, Husnul; Mujiono, Mujiono (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2024)
This study aims to find out a student who has learning difficulties in the perspective of the Koran. As a basis for the analysis are verses originating from the Koran. Learning difficulties can be influenced by various factors, ranging from learning styles, learning concentration problems, having unique learning preferences, different learning methods, health problems, lack of student motivation, environmental problems and emotional problems and learning interest. If the learning method used does not suit a person's learning style, they may have difficulty understanding and remembering information. Therefore, it is important for individuals to know their own learning style in order to be able to adopt appropriate learning strategies. This research is literature-based using qualitative methods with data sources from journal articles, books or observations of phenomena that occur in the world of education today.